Odpowiedzi

  • Użytkownik Zadane
2013-07-12T20:57:48+02:00

Pp = 1/2 * 4 * 3 = 6

 

Pb = 4 * 6 + 5 * 6 + 3 * 6

Pb = 24 + 30 + 18

Pb = 72

 

Pc = 2 * Pp + Pb

Pc = 2 * 6 + 72

Pc = 12 + 72

Pc = 84     ------- pole całkowite

 

V = Pp * h

V = 6 * 6

V = 36    ------  objetośc

1 5 1
2013-07-12T21:10:29+02:00

a=3

b=4

c=5   w podstawie trójkąt prostokątny o przyprostokątnych a, b

H=6

Pc=2Pp+Pb=2ab/2+(a+b+c)*H=ab+(a+b+c)*H

Pc=3*4+(3+4+5)*6=12+12*6=12+72=84 [j^2] pole całkowite

V=Pp*H

V=ab/2* H

V=3*4/2 *6=3*2*6=36[j³] objętośc

2 3 2